Sign-Coherence-Factor-Based Suppression for Grating Lobes in Through-Wall Radar Imaging - Liu, Jiangang; Jia, Yong; Kong, Lingjiang; Yang, Xiaobo; Liu, Qing Huo (IEEE geoscience and remote sensing letters, 2016)
A sparse and uniform multiple-input-multiple-output array is generally utilized in through-wall radar to implement real-time imaging of moving targets. However, the array sparsity with the interelement spacing much bigger than half a wavelength gives rise to grating lobe interference smearing the images. In order to enhance the signal-to-interference ratio, this letter introduces the sign coherence factor (SCF) to weigh through-wall images to suppress the grating lobes. The SCF is first proposed in medical ultrasound imaging and directly reflects the coherence of sign bits of all the transmit-receive channels in each pixel. Since the SCF calculated only by the sign bits, it has the smallest amount of computations compared with two other weighing factors, namely, the coherence factor (CF) and the phase coherence factor (PCF), which have been applied to through-wall imaging already. Moreover, the SCF has comparable performance in suppressing grating lobes with the PCF, much better than the CF. These two advantages make the SCF the most suitable for real-time imaging of moving targets. The experimental results with a two-transmitting eight-receiving stepped-frequency continuous-wave through-wall radar verifies the excellent performance of the SCF.